Investment of Time, Cost, and Dedication: A Case Study of Students of Mojokerto Fstar Dance Community - Ayu Nur Janna, Ainun; Handayani, Enie Wahyuning (Solah, 2025)
In the world of non-formal education, art communities are an important space for young people to express themselves and develop personal competencies. The Mojokerto Fstar Dance Community is one example of a non-formal art activity that is able to shape the values, character, and potential of the younger generation through involvement in modern dance. This study aims to examine the forms of investment of time, cost, and dedication made by students of the Mojokerto Fstar Dance Community as part of developing self quality, using the Social Cognitive perspective by Vygotsky L.S and A Human Capital Theory by Gary Becker. The method used is a descriptive qualitative approach through observation and in-depth interviews. The results showed that the involvement of participation in this community is not just a hobby, but a real form of non-formal investment that has long-term personal and social impacts. Community members, the majority of whom are aged 15 to 21, are willing to sacrifice time, incur personal expenses, and show high dedication to achieve achievements, both at the local and national levels. The dance project, which earned up to Rp20 million in four months, is clear evidence that training strategies, concept planning, and disciplined commitment can generate added value, not only financially, but also in terms of experience and self-identity. This research is expected to enrich the discourse of non-formal education and its contribution to human resource development through dance.